A novel enzymatic method discriminating wheat pre-harvest sprouting from Late Maturity alpha-amylase. (May 2022) - Mangan, D.; Draga, A.; Ivory, R.; Cornaggia, C.; Blundell, M.; Howitt, C.; McCleary, B.; Ral, J.P.
Abstract: The primary quality assessor of wheat grain is the Hagberg Falling Number (FN) method. This is a viscometric test surrogate for α-amylase activity. Despite being used for over sixty years, FN has been increasingly scrutinised due to its low throughput, poor reproducibility and inability to differentiate between the causes of low FN including Pre-harvest Sprouting (PHS) and Late Maturity α-Amylase (LMA). Our study describes initial efforts to analyse a specific wheat flour set tailored for the identification of enzymatic candidates that would allow discrimination between PHS and LMA affected grains. Using the sensitive enzyme-coupled assay substrate R-AMGR3, results suggest that α-glucosidase ( exo-α- glucosidase) is a potential enzyme marker candidate to specifically detect sprouted but not LMA-affected grain. Graphical abstract: Image 1